Complete genome of the onion pathogen Enterobacter cloacae EcWSU1. Issue 3 (November 2011) - Humann, Jodi; Wildung, Mark; Cheng, Chun-Huai; Lee, Taein; Stewart, Jane; Drew, Jennifer; Triplett, Eric; Main, Doreen; Schroeder, Brenda
Abstract Previous studies have shown that the members of theEnterobacter cloacae complex are difficult to differentiate with biochemical tests and in phylogenetic studies using multilocus sequence analysis, strains of the same species separate into numerous clusters. There are only a few completeE. cloacae genome sequences and very little knowledge about the mechanism of pathogenesis ofE. cloacae on plants and humans.Enterobacter cloacae EcWSU1 causesEnterobacter bulb decay in stored onions (Allium cepa ). The EcWSU1 genome consists of a 4, 734, 438 bp chromosome and a mega-plasmid of 63, 653 bp. The chromosome has 4, 632 protein coding regions, 83 tRNA sequences, and 8 rRNA operons.